THE CORRELATION BETWEEN REDUCTION IN FISSION-TRACK DIAMETER AND AREAL TRACK DENSITY IN VOLCANIC GLASS SHARDS AND ITS APPLICATION IN DATING TEPHRA BEDS - Sandhu A.S.; Westgate J.A. (My University, 1995)
The relationship between the reduction in fission-track diameter and the reduction in areal track density in hydrated glass shards has been investigated under varying annealing and etching conditions. A near 1:1 relation is observed for adequately etched tracks. Following laboratory heating of induced tracks, the partially reduced areal track density was renormalized (with error <10%) using the simple 1:1 relation between reduced diameter and reduced areal density. A similar approach was employed to correct for natural fading in spontaneous tracks. The apparent ages of 11 tephra beds, determined by applying the population-subtraction fission-track method to their hydrated glass shards, were corrected for partially lowered spontaneous track density in this way. These corrected ages are in good agreement with those obtained by the isothermal plateau fission track (ITPFT) method and other independent dating techniques.